2020
DOI: 10.1136/bmjopen-2019-032264
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac arrest after pulmonary aspiration in hospitalised patients: a national observational study

Abstract: ObjectiveTo study characteristics and outcomes among patients with in-hospital cardiac arrest (IHCA) due to pulmonary aspiration.DesignA retrospective observational study based on data from the Swedish Registry of Cardiopulmonary Resuscitation (SRCR).SettingThe SRCR is a nationwide quality registry that covers 96% of all Swedish hospitals. Participating hospitals vary in size from secondary hospitals to university hospitals.ParticipantsThe study included patients registered in the SRCR in the period 2008 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…An aetiology of aspiration and cancer has previously been shown to have particularly low survival. 24 , 30 The treatment of the underlying cause in patients who suffer from cardiac arrest due to acute abdomen or aortic dissection, is immediate surgery. To perform surgery in a patient who recently was resuscitated after a cardiac arrest is high-risk performance and the low survival among these patients is thus not surprising.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An aetiology of aspiration and cancer has previously been shown to have particularly low survival. 24 , 30 The treatment of the underlying cause in patients who suffer from cardiac arrest due to acute abdomen or aortic dissection, is immediate surgery. To perform surgery in a patient who recently was resuscitated after a cardiac arrest is high-risk performance and the low survival among these patients is thus not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…As described in previous studies, the registration in the SRCR occurs in two steps. 24 The first part of the registration is performed by a nurse or physician who were present at the scene of the cardiac arrest. This part contains information regarding treatments given during the resuscitation, place of the cardiac arrest, critical delay times, initial rhythm, if the patient was monitored at the time of the arrest, and if the patient received ROSC.…”
Section: Methodsmentioning
confidence: 99%
“…For the next most critical outcome of survival to discharge, 6 observational studies in people were identified that addressed the PICO question (very low quality of evidence, downgraded for very serious indirectness and serious imprecision). [164][165][166][167][168][169] In human hospitals, hospitalization in an unmonitored ward is associated with lower frequency of survival to discharge after IHCPA. 164,165 One particular at-risk group that experienced IHCPA secondary to aspiration pneumonia had a lower frequency of survival to discharge when CPA occurred in an unmonitored area.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…[164][165][166][167][168][169] In human hospitals, hospitalization in an unmonitored ward is associated with lower frequency of survival to discharge after IHCPA. 164,165 One particular at-risk group that experienced IHCPA secondary to aspiration pneumonia had a lower frequency of survival to discharge when CPA occurred in an unmonitored area. 165 The primary factor leading to the decision to implement continuous ECG monitoring in human patients was ongoing myocardial infarction, which may limit the applicability of these findings to dogs and cats.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Practical issues are also a considerable barrier to PC delivery in the ICU [18][19][20]23,29,32]. These issues include limited time for administrative tasks and documentation, disagreement about goals of care between HCPs, differences in nursing and medical approaches, and administrative policy treatment.…”
Section: Practical Issuesmentioning
confidence: 99%